Are Indian professional women financially literate and prepared for retirement?. Issue 4 (1st October 2020) - Baker, H. Kent; Tomar, Sweta; Kumar, Satish; Verma, Deepak
Abstract: This study examines the financial literacy level of Indian professional women and its relation to their retirement planning behavior. We use factor analysis and the Rasch model to evaluate the validity and reliability of a financial literacy scale. Additionally, we use multiple regression to examine the association between demographic characteristics and financial literacy with retirement planning. Our results reveal that the respondents display low levels of financial literacy as reflected by a lack of awareness about both basic and advanced financial concepts. Further, a woman's age, income, profession (financial), and understanding of advanced financial concepts are key factors associated with retirement planning behavior. The findings have implications for financial planning professionals, advisors, regulators, and policymakers in guiding women to make better retirement decisions.